Commissioner Fischler's initial response to the failure in Cancun - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Speaking immediately after the failure in Cancun, Agriculture Commissioner...